A novel terpenoid class for prevention and treatment of KRAS‐driven cancers: Comprehensive analysis using in situ, in vitro, and in vivo model systems. Issue 8 (15th April 2020) - Ganaie, Arsheed A.; Siddique, Hifzur R.; Sheikh, Ishfaq A.; Parray, Aijaz; Wang, Lei; Panyam, Jayanth; Villalta, Peter W.; Deng, Yibin; Konety, Badrinath R.; Saleem, Mohammad
Abstract: Inhibiting the disease progression in KRAS‐driven cancers after diagnosis has been a difficult task for clinicians to manage due to the lack of effective intervention/preventive therapies. KRAS‐driven cancers depend on sustained KRAS signaling. Although developing inhibitors of KRAS signaling has proven difficult in the past, the quest for identifying newer agents has not stopped. Based on studies showing terpenoids as modulators of KRAS‐regulated downstream molecular pathways, we asked if this chemical family has an affinity of inhibiting KRAS protein activity. Using crystal structure as a bait in silico, we identified 20 terpenoids for their KRAS protein‐binding affinity. We next carried out biological validation of in silico data by employing in situ, in vitro, patient‐derived explant ex vivo, and KPC transgenic mouse models. In this report, we provide a comprehensive analysis of a lup‐20(29)‐en‐3b‐ol (lupeol) as a KRAS inhibitor. Using nucleotide exchange, isothermal titration calorimetry, differential scanning fluorimetry, and immunoprecipitation assays, we show that lupeol has the potential to reduce the guanosine diphosphate/guanosine triphosphate exchange of KRAS protein including mutant KRAS G12V . Lupeol treatment inhibited the KRAS activation in KRAS ‐activated cell models (NIH‐panel, colorectal, lung, and pancreatic intraepithelial neoplasia) and patient tumor explants ex vivo. Lupeol reduced the three‐dimensional growth of KRAS ‐activated cells. The pharmacokinetic analysis showed the bioavailability of lupeol after consumption via oral and intraperitoneal routes in animals. Tested under prevention settings, the lupeol consumption inhibited the development of pancreatic intraepithelial neoplasia in LSL‐KRAS G12D/Pdx‐cre mice (pancreatic ductal adenocarcinoma progression model). These data suggest that the selected members of the triterpene family (such as lupeol) could be exploited as clinical agents for preventing the disease progression in KRAS‐driven cancers which however warrants further investigation.